Policy of suspiciousness –mobilization of educational reforms in Sweden. Issue 2 (4th March 2022) - Wahlström, Ninni; Nordin, Andreas
ABSTRACT: In this article, we explore the processes of transfer and translation of education policy in a study focusing on the relationship between the Organisation for Economic Co-operation and Development (OECD) and Sweden. The purpose of the study is to investigate how selective borrowing occurs both in terms of references to different types of knowledge sources underpinning the arguments and shared discourse formations. The data were obtained from two policy reports: an OECD review report of the Swedish school system and a Swedish follow-up report proposing actual school reforms. The method was twofold: first, mapping, categorizing, and counting all the textual references in the two documents; second, critically analyzing the discourses emerging in the two policy texts. The results show that international references play a significant role in substantiating arguments for Swedish education policy. Both policy texts share a policy discourse characterized by suspiciousness toward the professionalism exercised by teachers and local education authorities.